The Right of Pledge on Movable Items (Pignus) in Republic of Kosovo (European Journal of Social Sciences, 2019)
The pledge is an item right based on which its official holder – the pledgee may seek the payment of his/her claims from the item if those aren’t paid within certain time limit. The right of pledge in the Republic of Kosovo constitutes a complex occurrence which has various relations on which at one side is the pledgee creditor, and in the other side are debtor pledgor and other third persons. The role of pledge and its affirmation is related to most qualitative changes of claims. The right of pledge as item right in foreign item (iura in re aliena) makes a history only to a certain degree of economic and social development. In this degree of development there was a need and necessity to secure the other’s claims even de facto, by the hand item, by ”pledging” of an item. The creditor requires that his claims to the debtor be secured by obtaining of a pledge of debtor item. The debtor’s conjunction of creditor by obtaining debtor’s item is safer for the creditor to realize its claims, rather than when the debtor secured these claims by his/her personality, bail, personal insurance. In the Kosovo legal system there is possessory pledge, non-possessory pledge and the pledge over the rights.